Effects of Symbiosis Between Enterobacter cloacae UIA3 and Rice Plant Seedlings Under Different Salinity Treatments - Marwan, Nadia Amira Sabrina; Ponari, Md Hoirul Azri; Salleh, Mohd Syahmi; Amid, Azura; Rosli, Norsalsabila Mohd; Yunus, Muhamad Fahmi (AGRIVITA Journal of Agricultural Science, 2026)
Soil salinization is a significant constraint to global food security, with rice (Oryza sativa L.) being particularly prone to salinity stress. As a sustainable mitigation approach, plant growth-promoting rhizobacteria (PGPRs) are potential candidates for improving crop tolerance. This study investigates the performance of PGPR strain Enterobacter cloacae UIA3, noted for producing indole-3-acetic acid and nutrient solubilization, in establishing a symbiotic relationship with rice under salinity conditions. Three rice varieties, Pokkali, MR297, and IR64, under four salinity levels (0, 50, 100, and 150 mM NaCl) were analyzed for physiological response and symbiotic compatibility. A host-specific interaction was observed where the salt-tolerant Pokkali variety showed a strong positive association through enhanced root hair development and significant improvement in the growth of inoculated plants under stress. However, the salt-sensitive varieties of MR297 and IR64 showed severe root damage and exhibited minimal bacterial colonization. This indicates that the performance of E. cloacae UIA3 is effective mainly as bio-inoculation in salt-tolerant rice genotypes. Thus, host specificity is indispensable in the microbial strategy for saline agriculture. Overall, the results highlight avenues for PGPR strain E. cloacae UIA3 as an environmentally friendly bioinoculant under saline environments.